Analisis Proses Pelaksanaan Pembelajaran Daring Di Sekolah Dasar Pada Masa Pandemi Covid 19 - Handayani, Gita Widia; Maula, Luthfi Hamdani; Uswatun, Din Azwar (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This study aims to determine the process of implementing online learning during the Covid pandemic 19. This type of research is to use descriptive qualitative. The study was conducted in elementary schools namely SDN Dewi Sartika CBM, Sukabumi City in the Even Semester Academic Year of 2019/2020. The subjects used were teachers and fourth grade students with 32 students. The sampling technique used was purposive sampling. Data collection techniques used were interviews, questionnaires, and documentation to determine the process of implementation online learning carried out at home. The data collection instruments included interview guidelines, questionnaire sheets and documentation. Data analysis techniques use the stages of data reduction, data presentation, and conclusion drawing / verification. The results of this study were the process of implementing online learning in the Covid 19 pandemic period at SDN Dewi Sartika CBM, which has not been implemented properly, because there are still many obstacles faced, including the emergence of boredom, unfocused learning, lack of understanding of the material, cannot interact directly with the teacher and playing with friends, as well as limited network, signal, and quota constraints. As a result of the lack of understanding of teaching materials, some students experience a decrease in grades, although some other students have increased and even the average student gets a relatively consistent grade.